Perceived Life Skills Development – An Outcome of Madrassa Education in Pakistan - Naima Qureshi; Qudsia Kalsoom; Iffat Khalil (Journal of Islamic Thought and Civilization, 2021)
This study aims at assessing the development of life skills among madrassa students. The study has employed a mixed-method approach to explore the life skills of madrassa students. A questionnaire based on 5-point Likert type scale was used to measure selfreported life skills of 300 madrassa students. In addition, 20 semi-structured interviews were also carried out with madrassa students to explore their life skills. The quantitative data was analyzed by using descriptive statistics and qualitative data was interpreted through thematic analysis. Findings have revealed that the strongest life skill which madrassa students possess amongst all is effective communication skill followed by problem solving and decision-making. The least developed skill of madrassa students is creative thinking. The study findings suggest re-designing the curriculum of madrassa education to provide the students with more opportunities to polish their life skills especially creative thinking.